Comparison of the hanging-drop technique and running-drip method for identifying the epidural space in dogs. (March 2017) - Martinez-Taboada, Fernando; Redondo, José I.
Abstract: Objective: To compare the running-drip and hanging-drop techniques for locating the epidural space in dogs. Study design: Prospective, randomized, clinical trial. Animals: Forty-five healthy dogs requiring epidural anaesthesia. Methods: Dogs were randomized into four groups and administered epidural anaesthesia in sternal (S) or lateral (L) recumbency. All blocks were performed by the same person using Tuohy needles with either a fluid-prefilled hub (HDo) or connected to a drip set attached to a fluid bag elevated 60 cm (RDi). The number of attempts, 'pop' sensation, clear drop aspiration or fluid dripping, time to locate the epidural space (TTLES) and presence of cerebrospinal fluid (CSF) were recorded. A morphine–bupivacaine combination was injected after positive identification. The success of the block was assessed by experienced observers based on perioperative usage of rescue analgesia. Data were checked for normality. Binomial variables were analysed with the chi-squared or Fisher's exact test as appropriate. Non-parametric data were analysed using Kruskal–Wallis and Mann–Whitney tests. Normal data were studied with ananova followed by a Tukey's means comparison for groups of the same size. A p -value of < 0.05 was considered to indicate statistical significance. Results: Lateral recumbency HDo required more attempts (six of 11 dogs required more than one attempt) than SRDi (none of 11 dogs) ( p  = 0.0062). Drop aspiration was observed more often in SHDo (nine of 11 dogs) than in LHDo (two of 11 dogs) ( p  = 0.045). Mean (range) TTLES was longer in LHDo [47 (18–82) seconds] than in SHDo [20 (14–79) seconds] ( p  = 0.006) and SRDi [(34 (17–53) seconds] ( p  = 0.038). There were no differences in 'pop' sensation, presence of CSF, rescue analgesia or pain scores between the groups. Conclusion and clinical relevance: The running-drip method is a useful and fast alternative technique for identifying the epidural space in dogs. The hanging-drop technique in lateral recumbency was more difficult to perform than the other methods, requiring more time and attempts.